The Association between Obstructive Sleep Apnea and Metabolic Markers and Lipid Profiles - Wei‐Te Wu; Su-Shan Tsai; Tung‐Sheng Shih; Ming‐Hsiu Lin; Tzu‐Chieh Chou; Hua Ting; Trong-Neng Wu; Saou-Hsing Liou (2015)
Purpose The purpose of this study was to investigate the association between apnea-hypopnea index (AHI) and metabolic markers and whether the elevated risk of Metabolic Syndrome (MetS) is related to Obstructive Sleep Apnea (OSA). Methods This cross-sectional study recruited 246 male bus drivers from one transportation company in Taiwan. Each participant was evaluated by a polysomnography (PSG) test and by blood lipids examination. Severity of OSA was categorized according to the apnea-hypopnea index (AHI). Results The results showed that a 73.3% prevalence of MetS in OSA (AHI > 15) and a 80.0% prevalence of MetS in severe OSA (AHI > 30) were found. After adjusting for confounding variables, an increased level of Body-Mass Index (BMI) and two non-MetS cardiovascular risk factors, total cholesterol/HDL-C ratio and TG/HDL-C ratio was significantly associated with AHI in subjects with severe OSA. MetS was about three times to be present in subjects with severe OSA, even adjusted for BMI. Conclusions The findings showed a high prevalence of MetS in OSA among professional drivers, especially in the severe group category. BMI was the major contributing factor to OSA. However, the present study did not find a sensitive clinical marker of a detrimental metabolic profile in OSA patients.